Near-Field Ultrasonic Phased Array Deflection Focusing Based CFRP Wing Box Structural Health Monitoring - Yajie Sun; Yonghong Zhang; Chengshan Qian; Zijia Zhang (International Journal of Distributed Sensor Networks)
Near-field ultrasonic phased array theory is researched and utilized in the carbon-fiber wing box to identify the damage in the structure. Near-field ultrasonic phased array based structural health monitoring is researched to overcome the limitation of the far-field ultrasonic phased array in monitoring scope. The time delay of the theory and the process of the damage identification method are researched in detail. The recognition result is shown in a mapped image. The proposed method is applied in carbon fiber-reinforced polymer (CFRP) wing box to monitor the load in the structure. The experimental results show that the near-field ultrasonic phased array based structural health monitoring method is effective to identify the load position in the structure.